FDG PET-CT evaluation in neurolymphomatosis: imaging characteristics and clinical outcomes. Issue 2 (1st February 2018) - Davidson, Tima; Kedmi, Meirav; Avigdor, Abraham; Komisar, Orna; Chikman, Bar; Lidar, Merav; Goshen, Elinor; Tzila Zwas, S.; Ben-Haim, Simona
Abstract: Neurolymphomatosis (NL) often represents unidentified non-Hodgkin lymphoma relapses. Considering its severity, early detection and treatment are crucial. We outline one hospital's 18 F-FDG-PET-CT imaging findings of NL, along with the patients' clinical characteristics. Clinical records and imaging findings of 19 NL patients, PET-CT diagnosed, were retrospectively reviewed. Patient data, FDG-PET-CT findings and the presence of coexisting diseases, especially CNS involvement, were documented. Available MRI and clinical data verified the findings. All cases had increased linear FDG uptake along anatomic nerve sites. CTs showed varying degrees of corresponding soft-tissue-thickening. Clinical correlations also contributed to the diagnosis. In 4/19 patients, lymphoma presented with NL, in 15/19 it appeared with disease recurrence/progression. In 9/19, clinical symptoms suggested neural involvement while 10/19 had nonspecific symptoms. Eleven died of lymphoma within 0.9 years of diagnosis despite directed-therapy. Eight, however, survived up to 7.82 years post-diagnosis. Whole-body FDG-PET-CT can assist in early NL diagnosis, possibly enhancing survival.